Strategi Pengembangan Usaha untuk Meningkatkan Daya Saing pada UMKM Ekonomi Kreatif Aroma Bakery 3 di Kota Bengkulu - Erwani Yusuf; Yarni Julianti (Jurnal Multidisiplin Dehasen (MUDE), 2022)
The purpose of this study was to determine how the business development strategy to increase competitiveness in the Aroma Bakery 3 micro business in Bengkulu City. This study uses a qualitative method. Data collection techniques in this study are observation, interviews and documentation. The data analysis technique used is data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that Aroma Bakery 3 always carries out business development, even though the motive for changing circumstances such as motives in terms of characteristics and business capital has a very high influence on the business. There are always opportunities for business development. Aroma Bakery 3 takes advantage of business opportunities by making sales by canvassing stalls such as klontog shops and minimarkets as well as utilizing social media such as WhatsApp and Facebook as a tool to make sales. They held a training at Aroma Bakery 3 which was attended by the owner and all male employees. The emergence of the COVID-19 outbreak caused sales to decline due to social distancing, but business continued and did not fire employees.